مؤشّرُ الكثافةِ ودورهُ في تحديدِ الارتفاعاتِ الطابقيّة للأبنيةِ السكنيّةِ في مدينةِ دمشق - فاكوش, تمام; الصواف, ريم (Latakia University Journal -Engineering Sciences Series, 2019)
Although the term "Density" is a familiar word, but it is a highly complex one, due to its multiple definitions in various disciplines. The density at first glance in the urban and architectural world may mean organizing and building the largest number of dwellings given the urgent need for housing, A way of thinking about the physical structure of life and the needs of the people at a given location, which is mainly illustrated by the physical space of urban environments and architectural forms of different sizes and heights. This study discusses the relationship between the density and its potential in determining the height of the residential buildings and focuses on studying the local reality in comparison with the global experience. على الرغم من أنّ مفردة "الكثافة" كلمةٌ مألوفةٌ، إلاّ أنّها مصطلحٌ معقّدٌ بشكلٍ كبيرٍ، ويعودُ ذلك إلى تعدّد تعاريفهِ في مختلفِ الاختصاصاتِ، وقد تعني الكثافةُ للوهلةِ الأولى في العالم العمرانيّ والمعماريّ تنظيمَ وبناءَ أكبرَ عددٍ من المساكنِ بالنّظرِ إلى الحاجةِ الملحّةِ للإسكانِ، لكنّها أيضاً طريقةٌ للتفكيرِ حولَ البنيةِ الفيزيائيّةِ الحياتيّةِ للسّكّان واحتياجاتِهم في موقعٍ معينٍ، والتي تتوضحُ بشكلٍ أساسيٍّ في ذلكَ الحيّزِ الماديِّ المتمثّلِ في بيئاتٍ وعناصرَ حضريّةٍ وأشكالٍ معماريّةٍ ذات حجومٍ وارتفاعاتٍ مختلفةٍ. يناقشُ هذا البحثُ العلاقةَ بين مؤشّرِ الكثافةِ وإمكانيّاتهِ في تحديدِ الارتفاعاتِ الطابقيّةِ للأبنيةِ السكنيّةِ، إذ يُعرِّف بهِ وبمعاييرهِ، ويركزّ على دراسةِ الواقعِ المحلّيِّ في مقارنةٍ معَ التجربةِ العالميّةِ.